Kajian Organologi dan Teknik Permainan Slompret Jawa Oleh Abah Tetimo di Kota Binjai - Surbakti, Indra Yosia; Ginting, Yoe Anto; Sholikhah, Rahmatika Luthfiana (Jurnal Pendidikan dan Penciptaan Seni, 2026)
This study aims to describe the organology of the slompret used by Abah Tetimo and to analyze the playing techniques he employs in Binjai City. This study employs a qualitative method with a descriptive-analytical and ethnomusicological approach. Data were collected through participatory observation, in-depth interviews, and audio-visual documentation. The findings reveal that: (1) the slompret is classified as an aerophone under the Hornbostel-Sachs system (423.121, end-blown flute), constructed from bamboo, wood, stainless steel, and coconut shell or lontar palm, measuring 60–80 cm with five tone holes producing a loud and penetrative sound; (2) Abah Tetimo's playing technique encompasses five integrated dimensions: body posture with 30–60 degree elevation; diaphragmatic breath control including circular breathing; embouchure with 2–5 mm lip aperture; five-hole fingering with overblowing; and articulation comprising single tonguing, double tonguing, and legato.